1993
DOI: 10.1126/science.8266093
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in U6 snRNA that Alter Splice Site Specificity: Implications for the Active Site

Abstract: What determines the precise sites of cleavage in the two transesterification reactions of messenger RNA (mRNA) splicing is a major unsolved question. Mutation of the invariant G (guanosine) at position 5 of 5' splice sites in Saccharomyces cerevisiae introns activates cleavage at nearby aberrant sites. A genetic approach was used to test the hypothesis that a base-pairing interaction between the 5' splice site and the invariant ACAGAG sequence of U6 is a determinant of 5' splice site choice. Mutations in U6 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
255
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(272 citation statements)
references
References 39 publications
(50 reference statements)
13
255
0
4
Order By: Relevance
“…In the newly formed spliceosome, a specific sequence of U5 interacts with the exon sequences at the 5' and 3' splice sites (Newman and Norman, 1991;Newman and Norman, 1992;Wyatt et al, 1992;Cortes et al, 1993;Sontheimer and Steitz, 1993), and other sequences of U4 and U6 base-pair with each other. Then, before the first step of splicing occurs, the spliceosome undergoes dynamic changes, resulting in the departure of U1 and U4, and the formation of new duplexes, including those between U2 and U6, and between U6 and the 5' splice site (Hausner et al, 1990;Datta and Weiner, 1991;Wu and Manley, 1991;Yean and Lin, 1991;Madhani and Guthrie, 1992;Sawa and Abelson, 1992;Wassarman and Steitz, 1992;Lesser and Guthrie, 1993;Nilsen, 1994). The resulting conformational changes lead to the formation of the active spliceosome (complex B2), triggering the first step of splicing, where the bulged-out branch point adenosine nucleophilically attacks the phosphate at the 5' splice site.…”
Section: Introductionmentioning
confidence: 99%
“…In the newly formed spliceosome, a specific sequence of U5 interacts with the exon sequences at the 5' and 3' splice sites (Newman and Norman, 1991;Newman and Norman, 1992;Wyatt et al, 1992;Cortes et al, 1993;Sontheimer and Steitz, 1993), and other sequences of U4 and U6 base-pair with each other. Then, before the first step of splicing occurs, the spliceosome undergoes dynamic changes, resulting in the departure of U1 and U4, and the formation of new duplexes, including those between U2 and U6, and between U6 and the 5' splice site (Hausner et al, 1990;Datta and Weiner, 1991;Wu and Manley, 1991;Yean and Lin, 1991;Madhani and Guthrie, 1992;Sawa and Abelson, 1992;Wassarman and Steitz, 1992;Lesser and Guthrie, 1993;Nilsen, 1994). The resulting conformational changes lead to the formation of the active spliceosome (complex B2), triggering the first step of splicing, where the bulged-out branch point adenosine nucleophilically attacks the phosphate at the 5' splice site.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the S. cerevisiae splicing system indicate that, although base pairing with the U1 snRNA may not be a major determinant in defining the 59 splice site cleavage site, the U6 snRNA appears to be involved in the definition of the exact scissile bond (Séraphin et al+, 1988;Siliciano & Guthrie, 1988;Séraphin & Rosbash, 1990;Kandels-Lewis & Séraphin, 1993;Lesser & Guthrie, 1993)+ In agreement with this, there appears to be flexibility with respect to the position of U1 snRNA binding in the mammalian system+ For instance, U1 snRNAs with an altered 59 splice site recognition sequence (U1 snRNA nt 3-11), designed to base pair with sequences either upstream or downstream of the 59 splice site, can activate splicing of otherwise defective 59 splice sites mutated at positions ϩ3 to ϩ6 (Cohen et al+, 1994)+ Other mechanisms for early 59 splice site definition probably exist, as the U1 snRNP is not always required for splicing+ Inhibition of splicing upon depletion or inactivation of the U1 snRNP can be abrogated by the addition of high amounts of SR proteins, which appear to replace the U1 snRNP function and restore the splicing efficiency of some but not all pre-mRNA substrates (Crispino et al+, 1994;Tarn & Steitz, 1994)+ U5 snRNA, which enters the spliceosome as a component of the U4/U6+U5 tri-snRNP to form complex B, also contacts the 59 splice site (Fig+ 1)+ Phylogenetic comparisons show that the U5 snRNA contains an invariant U-rich sequence of 9 nt displayed in an 11-nt loop structure (Frank et al+, 1994)+ Data obtained from genetic experiments suggests that this sequence interacts with exon nucleotides immediately upstream of the 59 splice site in the pre-mRNA (Newman & Norman, 1991 and this is supported by the results from crosslinking experiments (Wassarman & Steitz, 1992;Wyatt et al+, 1992;Sontheimer & Steitz, 1993)+ In addition, the U5 loop sequence contacts the first 2 nt of the intron (Alvi et al+, 2001)+ Because the 59 exon region is not very well conserved, the interaction is believed to involve nonconventional base pairs+ The U5 snRNP may play a direct role in splice site selection based on the observation that, when normal 59 splice site definition is inhibited by mutation of the first 2 nt of the intron, the U5 loop sequence can influence the choice of the cleavage site (Cortes et al+, 1993)+ A potential protein factor involved in 59 splice site recognition is the U5 snRNP component Prp8, which has been shown to contact nucleotides on both sites of the 59 splice site scissile bond, including the first 2 nt of the intron, suggesting that the U1 and U5 snRNPs functionally collaborate in the recognition of the 59 splice site (Wyatt et al+, 1992;Teigelkamp et al+, 1995;…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct spliceosomal systems have co-existed in eukaryotic cells since at least the divergence of the plant and animal kingdoms (reviewed in Tarn & Steitz, 1997)+ These two systems act on pairs of mutually incompatible splice sites flanking pre-mRNA introns in eukaryotic nuclear genomes+ The large majority of introns in all known organisms are spliced by a wellstudied pathway requiring the function of the small nuclear RNAs U1, U2, U4, U5, and U6, as well as a large number of additional proteins+ In this pathway, multiple RNA-RNA interactions have been demonstrated to form between the splice site sequences and the snRNAs and between various snRNAs in the spliceosome (reviewed in Nilsen, 1998)+ One of the earliest interactions takes place between the 59 end of U1 snRNA and the 59 splice site via base pairing (Zhuang & Weiner, 1986;Seraphin et al+, 1988;Siliciano & Guthrie, 1988)+ A second base pairing interaction takes place between the sequence in the intron surrounding the site of branching and a region of U2 snRNA (Parker et al+, 1987;Wu & Manley, 1989;)+ Following these initial recognition events, a complex of U4, U5, and U6 snRNPs joins the nascent spliceosome and the combined assemblage undergoes several structural rearrangements+ During this portion of the spliceosome assembly process, the extensive base pairing between U4 snRNA and U6 snRNA is disrupted so that U6 snRNA can participate in base pairing to U2 snRNA (Hausner et al+, 1990;Datta & Weiner, 1991;Wu & Manley, 1991;Madhani & Guthrie, 1992)+ In addition, an adjacent sequence in U6 snRNA forms base pairs to the 59 splice site, which displaces U1 snRNA from the complex (Kandels- Lewis & Seraphin, 1993;Lesser & Guthrie, 1993;Hwang & Cohen, 1996)+ U5 snRNP interacts with exon sequences near the 59 and 39 splice sites, but apparently without substantial sequence specificity (Wyatt et al+, 1992;Sontheimer & Steitz, 1993;Newman, 1997)+ Thus, 59 splice site activation appears to be at least a two-step process in which U1 snRNP, probably in cooperation with additional factors, specifies the 59 splice site followed by U5 and U6 snRNP interactions that activate the site for reaction+ A striking feature of these RNA-RNA interactions is their apparent high degree of conservation throughout eukaryotic phylogeny+ These interactions have been studied in both yeast and human systems in vivo and in vitro by a variety of techniques (see Moore et al+, 1993 andNilsen, 1998 for reviews)+ These studies have demonstrated the stepwise assembly of the spliceosome and the roles of sequence elements in the...…”
Section: Introductionmentioning
confidence: 99%
“…The minor snRNA species U11, U12, U4atac, and U6atac appear to be the functional analogues of U1, U2, U4, and U6, respectively, at least to a first approximation+ U5 snRNA appears to be common to both systems+ Both in vivo and in vitro data support the idea that U12 snRNA interacts by base pairing with the highly conserved branch site sequence (Hall & Padgett, 1996;Tarn & Steitz, 1996a) and U11 snRNA interacts similarly with at least a portion of the 59 splice site sequence (Kolossova & Padgett, 1997;Yu & Steitz, 1997)+ Because these distinctive biochemical requirements define the two spliceosomal systems rather than any one feature of the intronic splice sites, we refer to the two classes of introns as U2-dependent or U12-dependent (Dietrich et al+, 1997)+ Recently, a novel U6-like snRNA called U6atac snRNA was identified that appears to be the functional analogue of U6 snRNA in the U12-dependent splicing system (Tarn & Steitz, 1996b)+ This finding has provided an opportunity to examine the conservation of some of the RNA-RNA interactions believed to be central to the splicing process+ One candidate interaction that emerged directly from the comparison of the U6 and U6atac snRNA sequences was the potential for base pairing between the U12-dependent 59 splice site and U6atac+ U6 snRNA contains a phylogenetically highly conserved sequence of ACAGA located just 59 of a region known to base pair with U2 snRNA in the spliceosome (Fig+ 1A)+ This sequence has been shown to interact, at least partially by base pairing, with the 59 splice site and, in particular, with the conserved G at position ϩ5 (Kandels- Lewis & Seraphin, 1993;Lesser & Guthrie, 1993;Hwang & Cohen, 1996)+ In U6atac snRNA, this sequence is replaced by AAGGAGA, which is also located 59 of a region that can potentially form base pairs with U12 snRNA and where a U12-U6atac in vitro crosslink has been mapped (Tarn & Steitz, 1996b)+ As shown in the shaded region of Figure 1B, this U6atac sequence has the potential to form several base pairs with the 59 splice site sequence of U12-dependent introns by displacing U11 snRNA+ In support of this idea, a recent crosslinking study detected an interaction between the 59 splice site of a U12-dependent intron and U6atac (Yu & Steitz, 1997)+ However, the site of crosslinking on U6atac was not determined and the functional significance of this crosslink remains to be shown+ To examine this potential U6atac snRNA-59 splice site interaction in an in vivo functional context, we examined the ability of specifically mutated U6atac snRNAs to rescue splicing of a U12-dependent intron containing splicing-defective mutations in the highly conserved 59 splice site sequence+ Our previous experiments looking for suppression of these intron mutants by mutant U11 snRNAs showed that splicing of some but not all 59 splice site mutants could be rescued (Kolossova & Padgett, 1997)+ We proposed that a possible reason for the inability of U11 snRNA mutations to suppress other 59 splice site mutations might be due to a requirement fo...…”
Section: Introductionmentioning
confidence: 99%